A CRITICAL REVIEW OF THE ERGOGENIC POTENTIAL OF CAFFEINE IN ATHLETIC PERFORMANCE - Wojciech Gawęda; Wiktoria Łobodzińska; Maciej Ficek; Justyna Adamczyk; Zuzanna Hamouta; Szymon Cholewiński (International Journal of Innovative Technologies in Social Science, 2025)
Purpose: This review provides a comprehensive synthesis of current evidence regarding the ergogenic properties of caffeine supplementation by critically evaluating its impact on exercise performance, fatigue attenuation, and post‑exercise recovery.Methodology: A systematic review of scientific literature published from 2015 was performed to examine the influence of caffeine on physical performance. The analysis includes randomized controlled trials, meta-analyses, and observational studies across a range of sports disciplines and population groups.Findings: Caffeine supplementation, particularly at doses of 3–6 mg/kg body mass taken approximately one hour before exercise, significantly enhances both aerobic and anaerobic performance. Meta-analyses confirm improvements in endurance, power output, muscular strength, and fatigue resistance across various athletic populations. Caffeine also reduces delayed-onset muscle soreness and may aid recovery, though its impact on heart rate variability post-exercise appears negligible. Individual responses vary based on sex, habitual intake, training status, and genetic factors.Conclusions: Caffeine is an effective and well-supported ergogenic aid for improving multiple dimensions of physical performance. Optimal benefits are achieved with moderate doses, while excessive intake may increase adverse effects without additional performance gains. Personalization of caffeine strategies based on individual characteristics is recommended to maximize efficacy and safety.